EVALUASI MEDIA PEMBELAJARAN DALAM PENGEMBANGAN TEKNOLOGI PEMBELAJARAN PAI - Burhan, Mohammad Nurul; Burhanuddin, Hamam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the concept, objectives, criteria, and steps of learning media evaluation within the context of developing Islamic Religious Education (PAI) learning technology. The method used is library research with a qualitative descriptive approach. Data sources consist of primary and secondary literature, including books, journal articles, and relevant academic documents, particularly the works of Richard E. Mayer (Multimedia Learning), Azhar Arsyad (Learning Media), Daniel Stufflebeam (CIPP model), and Benjamin S. Bloom (taxonomy of educational objectives). Data collection techniques employed documentation, while data analysis used content analysis. The findings show that the evaluation of PAI learning media is a systematic process to assess the feasibility, effectiveness, and suitability of media with the goals of Islamic education. The evaluation must cover four main aspects: material aspects (accuracy of scriptural evidence, curriculum alignment), technical aspects (display, user-friendliness), pedagogical aspects (interactivity, critical thinking), and Islamic value aspects (morals, sharia). The evaluation steps include: (1) determining evaluation objectives, (2) developing instruments, (3) conducting trials, (4) collecting response data, and (5) analyzing results and making continuous improvements. In conclusion, the evaluation of PAI learning media is an integral part of developing learning technology that is not only innovative but also meaningful and transformative, balancing cognitive, affective, and psychomotor achievements.